Sound bender - Oliver, Lin. (Scholastic Press, 2011)
After their parents are declared dead, Leo and his brother Hollis are taken in by a wealthy but distant step-uncle, and when, on his thirteenth birthday, Leo acquires the ability to hear sounds from the past when touching certain objects, he tries to use the skill to rescue a dolphin, whatever the cost.